2019
DOI: 10.3897/mycokeys.56.35554
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phylogeny reveal two novel Coryneum species from China

Abstract: Coryneum is currently the sole genus of Coryneaceae in Diaporthales, distinguished from other diaporthalean genera by transversely distoseptate brown conidia. However, Coryneum species are presently difficult to identify because of variability and overlap of morphological characters and the lack of sequence data for most described species. During fungal collection trips in China, 13 Coryneum isolates were obtained from cankered branches of Ilex and Quercus. Morphological and phylogenetic analyses (ITS, LSU, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…However, few studies have reported fungal infections on the branches and twigs of oak trees. More recently, 15 fungal pathogens, including in six genera (viz., Coryneum , Cryphonectria , Cytospora , Dendrostoma , Diatrype , and Diplodia ) have been implicated in causing dieback and canker disease in oak species (Fan et al, 2018; Jiang, Fan, et al, 2018, 2018; Jiang, Voglmayr, et al, 2019, 2019; Pan et al, 2019; Zhu et al, 2019, 2021). Although some canker and dieback diseases of oak have been discovered in the past, the accuracy of the identification cannot be confirmed because there are currently no living cultures or DNA sequences available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have reported fungal infections on the branches and twigs of oak trees. More recently, 15 fungal pathogens, including in six genera (viz., Coryneum , Cryphonectria , Cytospora , Dendrostoma , Diatrype , and Diplodia ) have been implicated in causing dieback and canker disease in oak species (Fan et al, 2018; Jiang, Fan, et al, 2018, 2018; Jiang, Voglmayr, et al, 2019, 2019; Pan et al, 2019; Zhu et al, 2019, 2021). Although some canker and dieback diseases of oak have been discovered in the past, the accuracy of the identification cannot be confirmed because there are currently no living cultures or DNA sequences available.…”
Section: Discussionmentioning
confidence: 99%
“…Notes: Coryneum is the only genus within the Coryneaceae (Jiang, Voglmayr, et al, 2018;Senanayake et al, 2017Senanayake et al, , 2018. The main feature distinguishes Coryneum from other genera in the Diaporthales is that it has transversely distoseptate brown conidia (Jiang, Voglmayr, et al, 2019). Most Coryneum species are discovered from cankers and dieback disease, which are commonly associated with Fagales species (Jiang, Voglmayr, et al, 2018;Senanayake et al, 2017).…”
Section: Other Main Genera Recorded From Oak Trees In Chinamentioning
confidence: 99%
“…Coryneum was recommended to be adopted as the generic name due to priority rather than Pseudovalsa (Rossman et al 2015 ). Most Coryneum species were considered strongly host-specific and associated with tree branch cankers (Jiang et al 2018 , 2019 ; Senwanna et al 2018 ).…”
Section: Taxonomymentioning
confidence: 99%
“…118 ). Coryneum fagi was phylogenetically close to C. ilicis , but they can be distinguished by the wider conidia of C. fagi ( C. fagi = 45–75 × 10–15.5 μm vs. 82–105 × 9.5–12.5 μm in C. ilicis ) (Jiang et al 2019 ).
Fig.
…”
Section: Taxonomymentioning
confidence: 99%
“…Diaporthales is well classified into families based on morphological and phylogenetic studies (Voglmayr and Jaklitsch 2014;Norphanphoun et al 2016;Voglmayr et al 2017;Fan et al 2018a;Senanayake et al 2018;Yang et al 2018a), and up to 32 families were accepted in the order Diaporthales (Jiang et al 2021). Specimens can be identified to specific level by morphological characters, such as transversely distoseptate brown conidia of Coryneum (Jiang et al 2018b(Jiang et al , 2019cSenwanna et al 2018); allantoid ascospores and conidia of Cytospora (Fan et al 2020); two-guttulate fusiform conidia of Diaporthe-like taxa (Fan et al 2018a;Yang et al 2018a, b); stromatic tissues turning to purple in 3% KOH of Cryphonectriaceae species (Chen et al 2013(Chen et al , 2018; dark acervular conidiomata with conspicuous central column of Melanconis-like taxa (Fan et al 2016;Jaklitsch and Voglmayr 2020).…”
Section: Introductionmentioning
confidence: 99%